(untitled) (Indian Journal of Arid Horticulture, 2017)
The pioneer white butterfly, Belenois aurota Fabricius, 1793 (Lepidoptera: Pieridae ), has found to be emerging as a major pest of ker (Capparis decidua) plant in arid region of India and causes over 70% damage to wild and cultivated ker plants. During the survey of pest incidence, the maximum incidence (86.67%) was observed in first fortnight of December and it was reduced to 11.67% in first fortnight of September in subsequent year. The average numbers of insects ranged between 1.33 to 10.33 larvae per branch of plant. Adults of this small butterfly were blacks and whites in color with black markings on both upper and under sides broader, the white spots on black apical area of fore wing often sub-obsolete above. Eggs were laid in batches on young shoots or new branches and were 1.74 mm in length, 1.55 mm in width and yellow in color when first laid. The length and width of 1st instar larvae were 2.05 mm and 0.47 mm, respectively and feed on branches gregariously. There were total of five instars. Pupae were 18.84 mm long and 4.92 mm wide. Adult females had a body length of 13.23 mm and a wingspan of 41.65 mm. Bodies of males were 11.54 mm long and their wingspan measured 38.72 mm.